2018
DOI: 10.1038/s41598-018-28140-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of drug release modulation from poly(2-oxazoline) micelles through ultrasound

Abstract: Among external stimuli used to trigger release of a drug from a polymeric carrier, ultrasound has gained increasing attention due to its non-invasive nature, safety and low cost. Despite this attention, there is only limited knowledge about how materials available for the preparation of drug carriers respond to ultrasound. This study investigates the effect of ultrasound on the release of a hydrophobic drug, dexamethasone, from poly(2-oxazoline)-based micelles. Spontaneous and ultrasound-mediated release of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 70 publications
(87 reference statements)
0
33
0
Order By: Relevance
“…It would, therefore, be conceivable that the structurally less dense SPA to PEGDA (6:4) cryogel microcarriers were able to stockpile more doxorubicin molecules within the core, as compared to the denser SPA to PEGDA (8:2) which only had molecules binding electrostatically to the outer surface of the polymeric network. Previous studies involving doxorubicin and other anticancer drugs have shown similar cases, where of binding affinity of drug to its carrier was found to be influenced by mechanical and, or, chemical properties depending on the accessibility of available functional groups for electrostatic binding (Gagliardi et al 2010;Newland et al 2018;Salgarella et al 2018;Zhang et al 2018b).…”
Section: Doxorubicin Release Studymentioning
confidence: 86%
“…It would, therefore, be conceivable that the structurally less dense SPA to PEGDA (6:4) cryogel microcarriers were able to stockpile more doxorubicin molecules within the core, as compared to the denser SPA to PEGDA (8:2) which only had molecules binding electrostatically to the outer surface of the polymeric network. Previous studies involving doxorubicin and other anticancer drugs have shown similar cases, where of binding affinity of drug to its carrier was found to be influenced by mechanical and, or, chemical properties depending on the accessibility of available functional groups for electrostatic binding (Gagliardi et al 2010;Newland et al 2018;Salgarella et al 2018;Zhang et al 2018b).…”
Section: Doxorubicin Release Studymentioning
confidence: 86%
“…Salgarella, Zahoranová et al. studied encapsulation of anti‐inflammatory drug dexamethasone (DEXA) into five different diblock and triblock copoly(2‐oxazoline)s. [ 160 ] Depending on the polymer structure, they observed formation of small micelles (diameter 35 nm), but also larger aggregates (hundreds of nm—several microns). The loading capacity ranged between 4.2 wt% (solubilization 0.44 g L −1 ) in case of copolymer p(EnOx‐BuOx) stat ‐ b ‐pMeOx to 14.7 wt% (solubilization 1.72 g L −1 ) in case of diblock copolymer pPrOx‐ b ‐pMeOx.…”
Section: Poly(2‐oxazoline)‐based Nanoformulationsmentioning
confidence: 99%
“…Increasing the number of pulses improved the animal survival rate compared to a single burst of LIFU; an increase in vascular permeability of tumors was additionally observed [24]. Salgarella et al investigated the synthesis and evaluation of five different forms of poly(2-oxazoline) micelles for a possible carrier of a drug delivery system triggered with ultrasound [25]. Micelles were tailored by controlling the ratio of hydrophilic and hydrophobic block copolymers and exhibited a significant release of dexamethasone.…”
Section: Physical Stimuli-responsive Systemsmentioning
confidence: 99%